PENGARUH KANDIDAT DAN IKATAN SOSIAL TERHADAP PERILAKU PEMILIH PEMULA DALAM PEMILIHAN LEGISLATIF TAHUN 2019 DI KECAMATAN TILATANG KAMANG - Irfan Saputra; M. Fachri Adnan (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2020)
This research aims to find out determine the effect of candidates and social ties on the behavior of novice voters in the 2019 legislative elections in kecamatan Tilatang Kamang. The background of the research is how the behavior of the novice voters sees from candidat image and the social ties that exist in their environment, Kecamatan Tilatang Kamang. This type of the research is quantitative research. The independent variable of this research are candidates and social ties, and dependent variable is novice voters behavior. The population of the research were the novice voter in Kecamatan Tilatang Kamang. Kecamatan Tilatang Kamang consists of three Kenagarian, Kenagarian Gadut, Kenagarian Koto Tangah, and Kenagarian Kapau. Sampling is by using the slovin formula and the sampling technique in this research is proporsional stratified random sampling. The sampling in the research totaled 96 novice voter in Kecamatan Tilatang Kamang. Data collection in this study use a questionnaire with a Likert scale. After that, the classical assumption test consist of normality test, linearity test, heteroscesdasticity test, multicoloniality test, and autocorrection test. Futhermor, a analysis multiples linear regression. The result showed that there was a significant the effect of candidates and social ties on the behavior of novice voter in the 2019 legislative elections in Kecamatan Tilatang Kamang.